Pengaruh Harga dan Lokasi Terhadap Keputusan Pembelian’ Fried Chicken Merk Sabana - Safriadi M Yunus Aks (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Sabana fried chicken is a street food business that is managed in a modern way in the form of a partnership. As the name suggests, Savana Fried Chicken is a food business like fast food in the form of a franchise model. A franchise is a form of business venture whose aim is to expand the reach of the business by increasing market share. The aim of this research is to see the extent to which price and location influence the decision to purchase the Savana brand of fried chicken at Jalan Komarudin, Pulo Gebang, East Jakarta. The research method used was using primary data, by distributing questionnaires and conducting direct interviews with 80 respondents. The data collection technique uses a purposive sampling technique (saturated sampling), namely collecting data as a whole on the population, because the number of respondents is small and less than 100 respondents. Data analysis uses multiple linear regression tests, correlation and determination tests, while the t hypothesis test is used to determine the influence partially and the F hypothesis test is used to determine the influence simultaneously. Based on the research results, it shows that price has a significant negative influence on consumers' decisions to buy Sabana brand Fried Chicken. Location has a significant positive influence on consumers' decisions to buy Sabana brand Fried Chicken. In general, it is concluded that the two variables, price and location, both partially and simultaneously, have a significant influence on consumer decisions in purchasing Sabana brand Fried Chicken which is located at Jalan Komarudin, Pulo Gebang, East Jakarta.